Character Education in the Mundong Dance by Christina Sri Asih Handayani at the Solah Bawa Art Studio in Sukoharjo Regency - Anya Kintani; Sawitri; Tri Widiatmi; Harsono (International Journal on Education Issues, 2026)
Purpose – This study analyzes the character education values embedded in the Mundong Dance choreographed by Christina Sri Asih Handayani at Sanggar Seni Solah Bawa, Sukoharjo Regency, and examines how those values can function as an arts-based medium for character formation. The study focuses on the dance accompaniment, movement, function, and meaning, and the character values these dimensions convey. Design/Methodology/Approach – The study employs a descriptive qualitative approach using a single instrumental case-study design. Data were gathered through participant observation, semi-structured interviews with four purposively selected key informants (the choreographer, the accompaniment composer, a studio trainer, and the studio owner), and documentation. Data were analyzed following the interactive model of Miles, Huberman, and Saldaña (data condensation, data display, and conclusion drawing), with Lickona’s tripartite framework of moral knowing, moral feeling, and moral action used as the analytical lens. Trustworthiness was established through source and technique triangulation, member checking, and an audit trail. Findings – The analysis identifies four interrelated character education values in the Mundong Dance—skill, religiosity, cooperation, and simplicity—each of which can be traced across Lickona’s moral knowing, feeling, and action components. The findings indicate that a structured and continuous arts-learning process at the studio mediates the internalization of these values, positioning the dance as more than entertainment. Originality/Value – The study contributes an explicit, framework-based mapping of how a locally rooted creative dance operationalizes character education, offering a transferable arts-based pedagogical model relevant beyond its immediate cultural setting.